Seni lukis kesenian dan seniman - Sudjojono, S., 1913-1986.; Soedjojono, S.; Yayasan Aksara Indonesia (Yogyakarta : Yayasan Aksara Indonesia, 2000)
Painting and painters in Indonesia.
Rev. ed. of: Seni loekis, kesenian dan seniman.
Keywords: Painting, Indonesian